Faktor-faktor yang mempengaruhi kesulitan dalam pembelajaran Maharah Kitabah dalam Program Khusus Pengembangan Bahasa Arab di Universitas Islam Negeri Maulana Malik Ibrahim Malang - Navisah, Dewi (Maliki Interdisciplinary Journal, 2024)
This study aims to describe the factors that influence the difficulties of students of the Faculty of Tarbiyah and Teacher Training non-degree of Arabic Language Education towards learning maharah kitabah at PKPBA UIN Malang. This research uses descriptive quantitative method with data obtained through questionnaires. The results showed that linguistic, psychological, and academic factors play a significant role in learning difficulties. Students' Arabic reading ability has the highest average score, while Arabic communication ability is the lowest, indicating difficulties in communication and word comprehension. Psychological factors such as lack of focus, motivation and interest contributed to the difficulties. Lack of active participation in class was the most influential academic factor. This research suggests the importance of a more interactive and supportive learning approach, and a focus on improving word comprehension and communication skills. By understanding and addressing these factors, it is hoped that the quality of Arabic language learning can be improved so that non-Arabic language students can better master writing skills. The results show that students experience significant difficulties in writing skills due to several interrelated factors. Linguistic factors include lack of vocabulary and difficulty in constructing sentences correctly. Psychological factors include lack of confidence and fear of making mistakes. While academic factors consist of a lack of hands-on practice in class and a lack of constructive feedback from lecturers. Improving writing skills is a fundamental need for non-major Arabic students, as mastering this skill can significantly improve their future academic and professional abilities.To improve the learning process, this study recommends implementing teaching strategies that focus on student interaction and active participation, as well as using modern educational technologies that help improve writing skills gradually. Lecturers should also create a supportive learning environment, which motivates students to actively participate and express their ideas freely and confidently. By adopting this approach, it is expected to improve students' ability in writing skills and reduce the difficulties they face in learning Arabic.